Analysis of Cinematic Techniques in the Implementation of Color Grading - Rohman, Muchamad Zainul (Formosa Journal of Computer and Information Science, 2025)
In the era of the digital world, where the development of technology in the visual field is currently very rapid, there are more and more ways to present information to the public. This is because the form of the delivery process is easy to understand to find or display information in the digital world. One of the most effective media in today's digital era is film, so a simpler and more effective means of socialization is needed, namely making documentary films. Pampang Cultural Village, one of the tourist and cultural areas of the Dayak tribe in Samarinda, East Borneo, Indonesia. A village with aesthetic educational value, especially related to history, traditions and cultural values of the ancestors which are still well preserved. In order to make this documentary film more interesting to watch and the audience can feel the meaning contained in this film, this film uses Cinematic Techniques by applying color grading. There are several techniques that can be considered in documentary films, namely content data in the form of audiovisual media, production processes including scenario writing, editing processes and directing techniques. With this documentary, it is hoped that local and foreign communities will know that there are educational and aesthetic tourist attractions about the customs and culture of the island of Borneo. This research will present the results of Cinematic Technique Analysis in the Implementation of Color Grading